PEMBATALAN PERKAWINAN KARENA KAWIN PAKSA MENURUT HUKUM KELUARGA ISLAM DI INDONESIA : Marriage Cancellation Due To Forced Marriage According To Islamic Family Law In Indonesia - Husen, Nur Afni; Setyaningsih (Faculty of Law, Universitas Trisakti, 2024)
The Tangerang Religious Court has decided to cancel marriage due to forced marriage with Number 2801/Pdt.G/2018/PA.Tng where the husband requests to cancel the marriage because the marriage was carried out by force. The 2 (two) main issues raised are whether forced marriages can be used as a reason for annulment of marriages based on Islamic family law in Indonesia and whether the decision of the Tangerang Religious Court is in accordance with Islamic family law in Indonesia or not. The research was conducted normatively with the nature of descriptive-analytical research and drawing conclusions using deductive logic methods. Forced marriage causes disputes in the household, so it can be a reason for filing an annulment of marriage. Tangerang Religious Court Decision No. 2801/Pdt.G.2018/PA.Tng states that the marriage annulment is granted so that, in this case, the marriage annulment has fulfilled the reasons according to the provisions of Article 71 letter (f) Compilation of Islamic Law which was caused by coercion. Thus, the decision is appropriate based on a review of Islamic family law in Indonesia.